The origins of modern Germany - Barraclough, G. (Basil Blackwell, 1962)
To provide such an insightful history of such a complicated country as Germany in a mere 460 pages is some feat. Especially valuable is Barraclough's illumination of Rome's, and a series of Popes', retrograde influence on Germany's early development.